Strength of semiconductors, metals, and ceramics evaluated by a microscopic cleavage model with Morse-type and Lennard-Jones-type interaction - Hess, Peter (Journal of applied physics, 2014)
An improved microscopic cleavage model, based on a Morse-type and Lennard-Jones-type interaction instead of the previously employed half-sine function, is used to determine the maximum cleavage strength for the brittle materials diamond, tungsten, molybdenum, silicon, GaAs, silica, and graphite. The results of both interaction potentials are in much better agreement with the theoretical strength values obtained by ab initio calculations for diamond, tungsten, molybdenum, and silicon than the previous model. Reasonable estimates of the intrinsic strength are presented for GaAs, silica, and graphite, where first principles values are not available.